BAU-STR Dryer: A Solution for Reducing Post Harvest Loss of Paddy in Bangladesh. - Kumer Saha, Chayan. (Tufts University. Tisch Library., 2020)
This presentation describes a new drying technology developed as a paddy drying technology alternative to traditional sun drying in Bangladesh.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy